Strategi Pembinaan Pustakawan Dalam Meningkatkan Kinerja Layanan Sirkulasi di Dinas Perpustakaan dan Kearsipan Kabupaten Aceh Barat - Merisa, Cut; Macella, Agatha Debby Reiza (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2022)
This study discusses the stategy of librarian development in improving circulation service performance, in accordance with its function, the library is a to store and disseminate information through a collection of libray matarials. Librarians are always led to improve competence and professionalism in carrying out their duties and functions, this is so that librarians can compete and work together. The purpose of this study was to find out how the stategy of the library in improving the performance of librarians in the  service sector, Through this stategy, Librarians are able to follow the are of information technology and become professionalism in the library field, This study uses descriptive qualitative methods in collecting data where this method  describes the description of words instead of numbers. The results of this research are : Resolution of Librarians in Facing Changes in the Circulition Service System in the Future, Performance Development, Implemented Cooperation, Development of  information Technology in the Field of Services through INLISLITE Applications, Cereer Development, Librarians Ability in Implementing Technology-Besed Library Management (INLISLITE), The process of recruiting librariasn, Budget allocation for librarians  development.  The results  obtained from the researchers, from the interview stge six (6) informants consisting of the librarians and the of sub-section.